2010
DOI: 10.1097/nmd.0b013e3181f4b2d7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and Stigma Associated With Mental Disorders in a South African Community Sample

Abstract: The aim of this study was to assess the awareness of, attitudes toward, and stigma associated with psychiatric disorders among South Africans. A convenience sample of 1081 members of the general public participated in the study. One of 10 vignettes portraying different psychiatric disorders with subtle or obvious symptoms was presented to each respondent. Schizophrenia was reported as being the most representative of a psychiatric disorder and post-traumatic stress disorder as the least representative. Psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 24 publications
8
46
1
Order By: Relevance
“…Furthermore, three participants very rarely referred patients to psychiatrists, preferring psychologists because patients 'just needed a space to talk' . This is in agreement with previous findings in the SA context, [2,9] which have indicated that people prefer to receive counselling rather than medication, particularly for mental illnesses such as depression.…”
Section: Collaboration With Traditional Healerssupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, three participants very rarely referred patients to psychiatrists, preferring psychologists because patients 'just needed a space to talk' . This is in agreement with previous findings in the SA context, [2,9] which have indicated that people prefer to receive counselling rather than medication, particularly for mental illnesses such as depression.…”
Section: Collaboration With Traditional Healerssupporting
confidence: 83%
“…Given the high prevalence of stigmatisation and lack of knowledge about mental illness, the participants in our study felt that campaigns to increase awareness were needed in Lenasia. Similarly, Mavundla et al [13] and Sorsdahl and Stein [9] have recommended that educational programmes are needed to inform communities about the causes of mental illness, coping methods and the importance of counselling and medication, as well as cultural conceptualisations of mental illness.…”
Section: Gps' Understanding Of Mental Illness and Its Causementioning
confidence: 99%
See 1 more Smart Citation
“…46 In a study investigating barriers to treatment in a nationally representative study in South Africa, the most common reason for not accessing mental health services was a low perceived need for treatment (93%). 47 Mental health literacy in South Africa has been investigated in community samples 48,49 , and in an HIV population. 50 This work indicates that common mental disorders are viewed as the result of everyday life challenges, rather than as treatable conditions.…”
Section: Adaptation Of Services To the South African Contextmentioning
confidence: 99%
“…People often refrain from finding the support and the care they need for fear of having negative labels attached to them by relatives or friends as a result of their mental health status Thornicroft, 2008). Negative attitudes are particularly strong against the use of drugs to treat mental disorders (Jenkins and Carpenter-Song, 2009;Sorsdahl and Stein, 2010). For example, the use of antidepressants to treat depression is often perceived as a sign of emotional weakness and inability to deal with problems (Castaldelli-Maia et al, 2011).…”
mentioning
confidence: 99%